the Influence of Psychomotricity on Child Development: Importance and Benefits: Importance and Benefits (REMUNOM, 2025)
This article aims to investigate the contribution of psychomotor education to the holistic development of children in early childhood education, addressing its implications on motor, cognitive, emotional, and social processing. Psychomotricity is defined as a field that explores the interrelation between motor, cognitive, and affective processes, using movement as an essential tool for the development of learning and socialization in children. The research was conducted through interviews with educators in the field and direct observations of psychomotor practices in school environments, with the goal of understanding the effects of this approach on the daily school routine. The data collection process involved interviews with teachers from different early childhood education classes, who reported the importance of psychomotor activities in the development of motor and emotional skills of students, as well as its positive influence on socialization and the construction of self-esteem. The observations helped to understand the practical application of these activities and highlight the tangible benefits for the holistic development of children. In the end, the results demonstrate that psychomotricity is a key tool in the school environment, promoting a more balanced and inclusive learning experience.